Sustainable Rangeland Management Toolkit for Resilient Pastoral Systems - Louhaichi, Mounir; Davies, Jon; Gamoun, Mouldi; Hassan, Sawsan; Abu-Zanat, Mahfouz; Neffati, Mohamed; Tadros, Maher; Ouled Belgacem, Azaiez; Rajabov, Toshpulot; Annouri, Laila; Al Rahahleh, Laith; Baqain, Razan; et al. (IUCN and ICARDA, 2022)
The toolkit advocates for a holistic and participatory multi-stakeholder approach that emphasizes the important role played by governance of rangelands using bottom-up landscape restoration. It also emphasizes the need to ensure that decisions are based on both indigenous knowledge and modern science to address site-specific challenges. Users have access to a collection of Sustainable Rangeland Management (SRM) practices aimed at achieving a neutral level of degradation (LDN) and offering a strong potential to rehabilitate and restore degraded rangeland ecosystems. The case studies describe how the toolkit is used to identify practical solutions that are integrated and socially accepted which foster community-based landscape restoration and sustainable livelihood development.